(untitled) (ALMUSTOFA: Journal of Islamic Studies and Research, 2025)
The exploitation of religion with the pretext of being the descendants of the Prophet Muhammad SAW occurs in various parts of the world, one of which is Indonesia, which is very dominant. The claim that the descendants of Habaib are nobler, superior to others, which is often legitimized in various social and political aspects, is one case that has attracted a lot of attention. This examines how the concept of descent is used as a tool of exploitation, how this impacts Indonesian Muslim society, and how this concept deviates from the true teachings of Islam. This article aims to open and reveal the social and theological realities of this phenomenon by using a qualitative literature study methodology. The results of the study indicate that the exploitation of religion in the name of descent creates social inequality and is very contrary to the teachings and values ​​of Islam which emphasize equality and piety as the main measure of a person’s nobility before the Lord of the universe.